METODOLOGI PENGEMBANGAN MODEL SIMULASI UNTUK EVALUASI KESELAMATAN PENUMPANG FREEFALL LIFEBOAT - Windyandari, Aulia (Gema Teknologi, 2011)
Aulia Windyandari, in paper simulation model of development method for passenger savety evaluation of freefaal lifeboat explain that since the launching procedure of Freefall Lifeboat (FFL) may have an impact with the water surface, the occupant injury is possible be occured in the evacuation process of the offshore structures.Â  The FFL shock acceleration has been conducted by the impact force when the lifeboat entry the water surface. If the shock acceleration over the human conciousness allowance, the serious injury will be happened during the FFL launching.According to the conditions, the IMO regulations have standard for the acceptance criteria of FFL shock acceleration induced by water entry impact load. The results measurement of Combined Acceleration Ratio Index (CAR) or Combined Dynamic Response Ratio Index (CDRR) should be comply with the IMO index criteria.In this paper, the methodology of FFL acceleration response prediction by the simulation model analysis will be proposed. The simulation model will be developed by using LS-Dyna code. The Simplified Arbitratry Lagrangian Eulerian Coupling will be used to define the coupling analysis between the Lifeboats (Lagrangian elements) with Water Fluids (the Eulerian Elements)Keywords: Free Fall Lifeboat, Response Acceleration, Impact Load